2015
DOI: 10.1189/jlb.3hi0115-018r
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 deficiency leads to increased eosinophils, alternative macrophage activation, and type 2 cytokine expression in adipose tissue

Abstract: Adipose tissue (AT) inflammation during obesity is mediated by immune cells and closely correlates with systemic insulin resistance. In lean AT, eosinophils are present in low but significant numbers and capable of promoting alternative macrophage activation in an IL-4/IL-13-dependent manner. In WT mice, obesity causes the proportion of AT eosinophils to decline, concomitant with inflammation and classical activation of AT macrophages. In this study, we show that CCR2 deficiency leads to increased eosinophil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 55 publications
4
31
1
Order By: Relevance
“…Under these conditions, we observed that Ccr2 −− mice had a slightly higher body mass (Figure 3A) without significant changes in adipose tissue mass, including eWAT and scWAT (Figure 3B). In agreement with previous studies (Bolus et al, 2015; Weisberg et al, 2006), we found that loss of CCR2 markedly decreased the numbers of total (~80%) and CD11c + macrophages (~78%) in the scWAT and eWAT of mice housed at thermoneutrality (Figure 3C, D and S5A–C). Similar reductions were also observed for total monocytes (~79–84%), Ly6C hi inflammatory monocytes (~90–97%), and Ly6C lo patrolling monocytes (~74–84%) in the scWAT and eWAT of Ccr2 −− mice housed at T a of 30°C (Figure 3E–G).…”
Section: Resultssupporting
confidence: 93%
“…Under these conditions, we observed that Ccr2 −− mice had a slightly higher body mass (Figure 3A) without significant changes in adipose tissue mass, including eWAT and scWAT (Figure 3B). In agreement with previous studies (Bolus et al, 2015; Weisberg et al, 2006), we found that loss of CCR2 markedly decreased the numbers of total (~80%) and CD11c + macrophages (~78%) in the scWAT and eWAT of mice housed at thermoneutrality (Figure 3C, D and S5A–C). Similar reductions were also observed for total monocytes (~79–84%), Ly6C hi inflammatory monocytes (~90–97%), and Ly6C lo patrolling monocytes (~74–84%) in the scWAT and eWAT of Ccr2 −− mice housed at T a of 30°C (Figure 3E–G).…”
Section: Resultssupporting
confidence: 93%
“…It must be acknowledged however, that a parasitic infection most certainly modulates a number of other immune cells, and it is unknown how propolis influences other immune processes; for this reason, it is not possible to by guest, on www.jlr.org Downloaded from say the increased eosinophils are definitively responsible for the improved glucose tolerance in such models as they were non-specific modulations of eosinophils. In our own studies, we found that despite specifically elevating numbers of WAT eosinophils in obese mice with either recombinant IL-5 (rIL-5) treatment or using CCR2 deficient mice, there was no improvement in glucose tolerance [72,110,123]. Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119].…”
Section: Downloaded Frommentioning
confidence: 99%
“…M2-like macrophages are traditionally associated with wound healing, but investigators have considered their anti-inflammatory phenotype to promote appropriate glucose and lipid control in WAT as well [43]. The M2-like phenotype of WAT macrophages is sustained through transcriptional activators such as PPARs, microRNAs such as miR-330-5p [69], adipose-derived stem cells [70], and cytokines such as IL-4 and IL-13 [32,[71][72][73][74]. Due to their proximity, M2-like macrophages are thought to interact with adipocytes, and may play roles in apoptotic clearance, angiogenesis, WAT development, antigen presentation, and inflammatory resolution [reviewed in [26,75]].…”
Section: Counterpoint To the Proinflammatory Adipose Tissue Macrophagmentioning
confidence: 99%
“…Clinically, whether manipulation of eosinophils will impact obesity-associated comorbidities deserves careful attention. In summary, the study by Bolus et al [6] confirms the protective role of eosinophils in obese adipose tissue and implicates a new role of CCR2 as one of the mechanisms controlling eosinophilmacrophage homeostasis in CLS of adipose tissue. This study also raises an interesting and challenging question in immunometabolism that remains to be addressed for most immune cells in adipose tissue: does leukocyte function differ based on its specific location?…”
mentioning
confidence: 57%